Dissecting the total cost of ownership of fully electric cars in Italy: The impact of annual distance travelled, home charging and urban driving. (May 2020) - Scorrano, Mariangela; Danielis, Romeo; Giansoldati, Marco
Abstract: The paper quantifies the importance for cost competitiveness of fully electric cars (BEVs) of three determinants of the total cost of ownership (TCO): the annual distance travelled (ADT), the percentage of urban trips, and the availability of a private parking space. The estimates are performed with reference to the Italian car market. We find that charging at home increases the break-even BEV manufacturer's suggested retail price (MSRP) relative to other propulsion systems by €2866-11, 466, depending on the ADT. Driving in urban areas increases the break-even BEV MSRP by €910-10, 314, depending on the ADT and on the referenced propulsion system. Taking into account the share of Italian drivers who own a garage and drive in urban areas, we find the cheapest BEVs are cost competitive without a subsidy with respect to the HEVs for 11.8% of the Italian drivers, but not with respect to the diesel and petrol cars, unless extremely high annual distances are driven. With the purchase subsidy recently introduced by the Italian government, the cheapest BEVs become competitive also with respect to the diesel cars, but not relative to the petrol cars, unless more than 12, 500 km are annually driven. Highlights: A Total Cost of Ownership model to evaluate electric cars' competitiveness. We compare electric, hybrid, diesel and petrol small-medium sized cars. We discuss the impact of annual distance travelled, urban travelling and charging habits. We study the impact of the Italian Ecobonus purchase subsidy. We estimate 11.8% of the Italian drivers enjoy electric cars' favorable conditions.